An Evaluation of Herbal Approaches for Managing Performance Anxiety in Singers - Alper Şakalar; Remziye Eda Kazancı (Konservatoryum)
This study aims to investigate the effectiveness of herbal treatment approaches in managing performance anxiety, a condition commonly observed among singers. In this context, the efficacy of 19 plants has been evaluated. Performance anxiety constitutes a significant challenge for performing artists and can negatively impact their professional performance. Conventional treatment methods do not always yield satisfactory results and may cause side effects. This situation highlights herbal remedies as a natural alternative with minimal side effects. Within the scope of the study, 19 plants used in the management of performance anxiety were examined. The anxiolytic, neuroprotective, cognitive function-supporting, sleep-regulating, antioxidant, and anti-inflammatory effects of these plants were assessed. The findings indicate that these plants may potentially help alleviate performance anxiety; however, side effects such as sedation, dizziness, and gastrointestinal discomfort should be carefully monitored during performance. Moreover, it is emphasized that the usage and timing of these herbal treatments should be planned with the support of a healthcare professional. The research suggests that herbal therapies could provide a significant alternative for singers experiencing performance anxiety, though individual responses to these treatments may vary. Future studies could explore the long-term effects of these plants and individual differences more comprehensively, contributing to the development of safer and more effective protocols for performing artists. In this regard, the study offers practical recommendations for the safe and informed use of herbal approaches and makes a notable contribution to the literature.